Обломов: [роман] / Иван Гончаров - Гончаров Иван Александрович (Серия "Русская классика", 2016)
Экземпляры: аб. (20160608) / Инвентарный номер: 57026 / Цена: / Сис.шифр: 84(2Рос=Рус)1-44 / Авт.знак: Г 65 / ГРНТИ: 17.82.31 / ББК: 84(2Рос=Рус)1-44